Design of multi-section luffing apple pruning equipment and cutting test of the key components - Tong, Siyuan; Li, Wenbin; Wang, Yaxiong; Zhang, Lei; Kang, Feng (International Journal of Agricultural and Biological Engineering, 2024)
In order to reduce the labor intensity and improve the efficiency of pruning, this study designed a multi-section luffing apple pruning equipment suitable for apple orchards in hilly and mountainous areas of China. In the essay, the structure and working principle of the equipment are expounded, the cutter was analyzed, and the parameters were determined. Using the self-made test bench to simulate the field experiment, this study selected the ratio of cutting speed to feeding speed and feeding speed as the influencing factors and took the cut-off rate, cutting efficiency and cutting power as the objectives to carry out single factor experiment and quadratic regression orthogonal experiment. The test results show that the cutting power increases with the increase of ratio of cutting speed to feeding speed, and the cut-off rate and cutting efficiency first increase and then decrease. As the feeding speed increases, the cutting efficiency and power increase, and the cut-off rate decreases. When the cut-off rate was greater than 80%, the optimal combination of operating parameters was the feeding speed of 0.55 m/s and ratio of cutting speed to feeding speed of 1.29. Under this combination, the cut-off rate was 84.9%, the cutting efficiency was 13.1, and the cutting power was 175.7 W. The error between the predicted target value of the model and the average measured target value was less than 7%, so the test results are reliable. According to the obtained optimal operating parameters, the actual cutting experiment of the pruning equipment in the field was carried out, and the cutting rate was 96.3%, which meet the design requirements. This study can also meet the needs of mechanized pruning of fruit trees with different crown shapes, improve the applicability of pruning equipment, and provide support for the development of mechanized pruning equipment in China. Keywords: apple, pruning equipment, cutting test, optimal parameters, regression analysis DOI: 10.25165/j.ijabe.20241701.7988 Citation: Tong S Y, Li W B, Wang Y X, Zhang L, Kang F. Design of multi-section luffing apple pruning equipment and cutting test of the key components. Int J Agric & Biol Eng, 2024; 17(1): 109-117.